Evaluating the Updip Extent of Large Megathrust Ruptures Using Pcoda Levels. Issue 10 (23rd May 2019) - Lay, Thorne; Rhode, Andrea
Abstract: When slip at shallow depth occurs during large subduction zone thrust events, P wave energy enters the water layer and establishes pwP, the reverberating waves called "water bounces" that follow pP . For water depths ≥5–6 km (i.e., near the trench) above the shallow slip, pwP manifests in a strong ~10‐s period ringing that can persist for minutes into the teleseismic P wave coda at all azimuths. Deeper slip can generate shorter‐period pwP ringing at trenchward azimuths. At large distances, P coda windows have several‐minute‐long intervals free of secondary arrivals. We consider rms P coda /rms P amplitude ratios at distances from 80° to 120° as a potential proxy for occurrence of shallow slip for 39 M W 7.5+ megathrust earthquakes from 1990 to 2016 with estimated slip distributions. Ratios for the 15‐ to 7‐s‐period band have a strong bimodal distribution, with higher average P coda / P amplitudes observed for ruptures with slip extending to shallow depth. Plain Language Summary: We establish a feature of teleseismic signals that indicates occurrence of slip at shallow depth near the trench for large subduction zone underthrusting earthquakes. This is valuable for rapid assessment of tsunami excitation, augmented for an event of given seismic moment by shallow faulting under deep water. The feature that is explored involves generation of ringing coda in the P wavefield for near‐trench slip, associated with acoustic reverberations ( pwP ) in the deep ocean layer above the slip zone. Essentially, slip on the shallow plate boundary generates booming 10‐s‐period sounds that can be observed teleseismically at all azimuths. Deeper slip generates shorter‐period sounds preferentially observed seaward of the slip. By measuring the relative signal power in the P wave coda compared to the direct P wave in the 15‐ to 7‐s‐period band, a simple proxy for whether slip occurred at shallow depth is obtained. This is calibrated using 39 major underthrusting events for which the slip distribution is known independently. Higher P coda/ P amplitudes indicate at least some shallow slip during the rupture, which can be useful for rapid tsunami warning and for evaluating the updip limit of faulting of historic and modern earthquakes to aid in earthquake hazard assessment. Key Points: Slip on megathrust faults under deep water near the trench generates persistent P wave coda reverberations isolated at distances >80° Average rms P coda /rms P amplitude ratios are compared for 39 M W  >= 7.5 megathrust ruptures that have estimates of their slip distribution Observation of high P coda / P ratios strongly correlates with coseismic rupture having shallow slip and likely enhanced tsunami excitation